Investigating How Auditory and Visual Stimuli Promote Recovery After Stress With Potential Applications for Workplace Stress and Burnout: Protocol for a Randomized Trial - Byun, Kunjoon; Aristizabal, Sara; Wu, Yihan; Mullan, Aidan F.; Carlin, Jeremiah D.; West, Colin P.; Mazurek, Kevin A. (Frontiers in Psychology, 2022)
Background: Work-related stress is one of the top sources of stress amongst working adults. Relaxation rooms are one organizational strategy being used to reduce workplace stress. Amongst healthcare workers, relaxation rooms have been shown to improve perceived stress levels after 15 minutes of use. However, few studies have examined physiological and cognitive changes after stress, which may inform why relaxation rooms improve perceived stress. Understanding the biological mechanisms governing why perceived stress improves could lead to improved individualized and organizational strategies to address workplace stress. Objective: The purpose of this research study is to understand how physiological measures, cognitive performance, and perceived stress change after acute stressful and whether certain sensory features of a relaxation room are more effective at promoting recovery from stress. Methods: 80 healthy adults will perform a stress induction task (Trier Social Stress Test, TSST) to evaluate how physiological and cognitive responses after stress are affected by sensory features of a relaxation room. After the stress induction task, participants will recover for 40 minutes in a MindBreaks relaxation room containing auditory and visual stimuli designed to promote relaxation. Participants will be randomized into four cohorts to experience either auditory and visual stimuli; auditory stimuli; visual stimuli; or no stimuli in the room. Measures of heart rate and neural activity will be continuously monitored using wearable devices. Participants will perform working memory assessments and rate their perceived stress levels throughout the experiment. These measures will be compared before and after the stress induction task to determine how different sensory stimuli affect the rate at which individuals recover. Results: Recruitment started in December 2021 and will continue until December 2022 or until enrollment is completed. Final data collection and subsequent analysis are anticipated by December 2022. We expect all trial results will be available by early 2023. Discussion: Findings will provide data and information about which sensory features of a relaxation room are most effective at promoting recovery after acute stress. This information will be useful in determining how these features might be effective at creating individualized and organizational strategies for mitigating the effects of workplace stress.